Formas de adubação de semeadura de milho para as safras de verão e segunda safra - Peron, Gustavo de Carvalho (2018)
The Maize (Zea mays l.) yield is strongly influenced by the management of fertilization to which it is submitted. Studies have shown that there are increasing responses in productivity to improvements in fertilizer management. Soil Nutrients availability and its disposition at appropriate levels determine the productivity final result. Fertilization management such as band placement (localized fertilizer) or broadcasting fertilizers (on the soil surface) have direct interference in the nutrients use by the roots and also causes significant differences in the operational yield of maize sowing. Therefore, it is necessary to seek a balance between the operational yield and the better utilization of fertilization by maize. This study aimed to evaluate alternative sowing fertilization in maize grain yield. The study was carried out at a grain - producing farm in the Triângulo Mineiro region, in Serra do Salitre city, Minas Gerais state. A total of 33 maize hybrids wer e evaluated in two types of fertilization management of sowing: band fertilizer next to sowing and fertilization to the sowing in pre-sowing. The experimental design used was randomized complete block design with three replications, in a 2 x 33 factorial experiment, it was carried out in 4 subsequent crops in the agricultural years of 2015/2016 and 2016/2017. The experimental plots measured 1000 m². It was evaluated a productivity in kg.ha-1 and after a data collection for the statistical analysis by SAS software. The sowing fertilization done in a band placement in the furrow provides a higher grain yield than the broadcasting fertilizer, regardless of the sowing or harvest season. There was no interaction between hybrids and the forms of fertilization of sowing. Considering all the experiments conducted, the hybrids that had the highest grain yield averages were 2B810 PW, AS1633 PRO3, DKB 310 PRO3 and Conventional P3898.